Methods for development work and research a new guide for practitioners - Mikkelsen, Britha (SAGE, 2005)
This revised edition incorporates new lessons learned regarding the merits and pitfalls of development work, including participatory methods and development in practice. It continues to offer valuable and practical guidance combined with critical reflection on methods for development work and research